A double-sided heat-conducting gasket with different properties and a preparation method thereof

By using uncoated fiberglass cloth as a support material and controlling the concentration and molecular weight of silicone reactants, a double-sided thermally conductive pad is formed through multiple calendering and vulcanization processes. This solves the problems of oil separation and porosity in existing technologies and achieves a thermally conductive pad with high strength and adhesion.

CN117090060BActive Publication Date: 2026-03-17SUZHOU YANGCHI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310999287.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2026-03-17
Estimated Expiration
2043-08-09

AI Technical Summary

Technical Problem

In the existing technology, silicone cloth and thermally conductive silicone filler permeate each other during the vulcanization process, causing small grease molecules to precipitate on the surface of the thermal pad, and dense small pores to appear at low thickness, which cannot meet the requirements of high strength and adhesion.

Method used

Using uncoated fiberglass cloth as the support material, the concentration and molecular weight of the organic reactants of silicone on both sides of the fiberglass cloth are controlled, and the cloth is calendered and vulcanized in stages to form thermally conductive pads with different properties on both sides. This ensures that one side has good adhesion and the other side has high strength, avoiding pores and oil separation.

Benefits of technology

It effectively reduces the oil separation rate and dense pores on the surface of the thermal pad, improves the performance stability of the pad, and exhibits good adhesion and high strength, especially at thicknesses below 0.5 mm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117090060B_ABST
    Figure CN117090060B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of heat dissipation devices, and particularly relates to a double-sided heat-conducting gasket with different properties and a preparation method thereof. The present application does not use the existing silica cloth as a reinforcing material, but uses a glass cloth blank without additional material and without a coating process as a medium for supporting two kinds of silica gel. The concentration of organic reactants and the molecular weight of silica gel on both sides of the glass cloth are calculated and controlled, and then the silica gel is subjected to stepwise calendering and vulcanization, so as to form a double-sided heat-conducting gasket with different properties on both sides, one side having adhesion and no air holes, and the other side having high strength and less oil bleeding. The present application firstly reduces the oil bleeding rate on the surface of the gasket with the traditional silica cloth as the reinforcing material, and secondly effectively reduces the dense air holes on the surface of the high-heat-conducting gasket with the additional reinforcing material below 0.5 mm, thereby enhancing the stability of the gasket performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of heat dissipation device technology, specifically relating to a double-sided thermally conductive pad with different properties and its preparation method. Background Technology

[0002] With the rapid development of the new energy market, the new energy industry is expanding at an astonishing pace. Continuous innovation in new energy technologies is leading to increasingly rapid changes in the demand for different types of thermal interface materials. Currently, there is a need for a thermally conductive pad with different properties on both sides. One side needs good adhesion, while the other side requires high strength, impact resistance, and minimal oil exudation. The pad thickness must be controlled to below 0.5 mm. 2. Existing technology uses silicone cloth as a reinforcing material, with the silicone layer providing strength. The other side is bonded to thermally conductive silicone filler through calendering and vulcanization. However, the problem with existing technology lies in the interaction between the silicone cloth and the thermally conductive... The organic reactive components in the silicone filler are similar, and the vulcanization process is equivalent to a secondary vulcanization. They can penetrate each other, thus the silicone layer affects the cross-linking reaction of the thermally conductive layer. Moreover, the molecular weight of the organic reactants in the original thermally conductive silicone filler is relatively low, and the cross-linking density is relatively low. After a period of time, small grease molecules are more likely to be precipitated on the surface of the thermally conductive pad. In addition, since the silicone layer is a relatively complete interface after one vulcanization, it blocks the thermally conductive filler layer from escaping a small number of air bubbles. As a result, when making a thinner pad, an uncontrollable phenomenon of dense small pores occurs. 3. In order to solve this problem, a new process and a new formula are adopted. Summary of the Invention

[0003] The existing technical problem is that silicone cloth is a chemically processed finished product, and its main organic component is also silicone. When it is calendered and vulcanized with thermally conductive silicone filler during use, the organic reactants in the thermally conductive filler have relatively small molecular weights. Due to the influence of the organic matter in the silicone layer of the silicone cloth, the organic molecules in the microstructure separate and migrate, resulting in a relatively lower overall cross-linking density. This leads to the precipitation of small oil molecules that are not fully cross-linked after a period of time. Furthermore, during the calendering of the thermally conductive silicone filler, the silicone layer cannot allow a small number of air bubbles to escape, thus making it impossible to avoid the appearance of irregular and dense small pores in the thermally conductive silicone layer after vulcanization.

[0004] Therefore, this invention does not use existing silicone cloth as a reinforcing material, but instead uses uncoated fiberglass cloth without additional materials as a medium to support two silicone materials with different properties. By calculating and controlling the concentration and molecular weight of organic reactants in the silicone materials on both sides of the fiberglass cloth, the invention performs multiple calendering and vulcanization processes to form a double-sided thermally conductive pad with two different properties: one side is adhesive and non-porous, and the other side has high strength and low oil separation.

[0005] To address the aforementioned technical problems, this application provides the following technical solution:

[0006] A method for preparing a thermally conductive pad with different properties on both sides includes the following steps:

[0007] S1: By weight, 10-30 parts of low molecular weight vinyl silicone oil (low viscosity silicone oil), 1-2 parts of polymethyltriethoxysilane and 0.5-4 parts of hydrogen-containing silicone oil are mixed once, and then 10-50 parts of aluminum hydroxide and 40-100 parts of aluminum oxide are added for a second mixing to obtain the mixed raw materials.

[0008] S2: Add 0.5-1 part of platinum catalyst to the mixed raw materials and mix three times to obtain thermally conductive silicone resin I;

[0009] S3: The thermally conductive silicone resin I obtained in step S2 is coated on one side of the fiberglass fabric and then calendered and vulcanized once, and then wound up to obtain a single-layer thermally conductive pad with adhesive properties.

[0010] S4: The surface of the single-layer thermally conductive pad with adhesive properties is coated with thermally conductive silicone resin I on the side that is not coated with thermally conductive silicone resin II, and then subjected to secondary calendering and vulcanization to obtain the thermally conductive pad with different properties on both sides; the thermally conductive silicone resin II is obtained by mixing thermally conductive silicone resin I with 20-40 parts of ultra-high molecular weight vinyl silicone oil (ultra-high viscosity silicone oil).

[0011] Preferably, in step S1, the mixing temperature is 20-25℃, the rotation speed is 15-35 rpm, and the time is 8-15 min.

[0012] Preferably, in step S1, aluminum hydroxide and aluminum oxide are dried at 110-130°C for 1-2 hours before the first mixing.

[0013] Preferably, in step S1, the secondary mixing method is stirring, which is carried out 2-3 times, each time for 8-20 minutes.

[0014] Furthermore, during the secondary mixing, after the first stirring is completed, a vacuum is drawn until the vacuum level reaches below -0.1 MPa.

[0015] Preferably, in step S2, the three mixing methods are stirring, and the stirring time is 14-16 minutes.

[0016] Preferably, in step S3, the temperature of the first calendering vulcanization is 90-120℃.

[0017] Preferably, in step S4, the mixing is carried out using a mixer for 8-15 minutes.

[0018] Preferably, the low molecular weight vinyl silicone oil has a viscosity range of 100-500 CPS and a molecular weight of 5000-20000; commercially available silicone oil products can be purchased according to viscosity.

[0019] Preferably, the ultra-high molecular weight vinyl silicone oil has a viscosity of 100,000-200,000 CPS and a molecular weight of 100,000-250,000; it is commercially available.

[0020] The present invention also provides a thermally conductive pad with different properties on both sides prepared by the above preparation method.

[0021] Because the fiberglass preform has good permeability and the thermally conductive silicone resin II contains ultra-high molecular weight organic reactants, during the vulcanization process, small molecule oils that have not fully reacted due to incomplete cross-linking of the thermally conductive silicone layer can penetrate into the strength layer for secondary vulcanization. Furthermore, because the silicone layer vulcanizes first, small air bubbles are discharged from the strength layer, which has less resistance and is not yet vulcanized due to the presence of inorganic fillers. This results in a novel double-sided thermally conductive pad with different properties, where one side has good adhesion and no pores, while the other side requires high strength, impact resistance, and effective control of surface oil separation.

[0022] The technical solution of the present invention has the following advantages compared with the prior art:

[0023] This invention firstly reduces the oil separation rate on the surface of gaskets reinforced with traditional silicone cloth, and secondly effectively reduces the occurrence of dense pores on the surface of high thermal conductivity gaskets with additional reinforcing materials less than 0.5 mm thick, thereby enhancing the stability of gasket performance. Attached Figure Description

[0024] Figure 1 This is an image of the silicone layer of a standard silicone cloth calendered gasket.

[0025] Figure 2 This is a picture of the silicone surface of a standard silicone cloth calendered gasket.

[0026] Figure 3 The image shows a thermally conductive pad with different properties on both sides prepared according to the present invention.

[0027] Figure 4 This is an oil chromatography diagram showing the strength of the double-sided thermally conductive pads with different properties prepared according to the present invention.

[0028] Figure 5 This is a schematic diagram of the structure of the double-sided thermally conductive pad with different properties prepared according to the present invention.

[0029] Explanation of reference numerals in the attached drawings: 1-thermal conductive silicone resin I, 2-glass fiber preform, 3-thermal conductive silicone resin II. Detailed Implementation

[0030] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0031] Example 1

[0032] (1) Weigh out 20 parts of 170000 CPS viscosity vinyl silicone oil (molecular weight approximately 160000), 10 parts of 500 CPS viscosity silicone oil (molecular weight approximately 17000), 0.5 parts of polymethyltriethoxysilane, 0.5 parts of hydrogen-containing silicone oil, 0.5 parts of platinum catalyst, 40 parts of aluminum hydroxide and 50 parts of aluminum oxide respectively, and then place aluminum hydroxide and aluminum oxide in an oven at 120℃ to dry for 1 hour.

[0033] (2) Weigh out low molecular weight vinyl silicone oil, polymethyltriethoxysilane, and hydrogen-containing silicone oil and pour them into a mixer. Connect a constant temperature water tank and control the temperature at 20℃. Control the mixer speed at 15 rpm and stir for 8 minutes. After stirring, add dried aluminum hydroxide and aluminum oxide to the mixer and stir twice, 8 minutes each time. After the first stirring, turn on the vacuum pump to ensure that the vacuum degree in the mixer reaches below -0.1 MPa and continue stirring. After stirring, add platinum catalyst and stir for 15 minutes. After completion, thermally conductive silicone resin I is obtained.

[0034] (3) Divide the thermally conductive silicone resin obtained in step (2) into two equal parts, A and B. Add the ultra-high molecular weight vinyl silicone oil weighed in (1) and an additional 4 parts of hydrogen-containing silicone oil to B and stir in a mixer for 8 minutes. After stirring, thermally conductive silicone resin II is obtained. First, press the A obtained in step (2) into a calendering device. Set the oven temperature to 90°C, add glass fiber preform, set the calendering thickness, which is thicker than the strength layer, and perform calendering and vulcanization to obtain a conventional single-layer thermally conductive pad with added glass fiber. This single-layer thermally conductive pad has the adhesion required by the customer.

[0035] (4) The single-layer thermally conductive pad obtained in (3) is wound up and then transferred to a calendering device for secondary calendering. The thermally conductive silicone resin II obtained in step (3) is then calendered and then placed in an oven for secondary vulcanization to produce a new type of double-sided thermally conductive pad with different properties.

[0036] Example 2

[0037] (1) Weigh out 22 parts of vinyl silicone oil with a viscosity of 130000 CPS (molecular weight approximately 145000), 12 parts of vinyl silicone oil with a viscosity of 350 CPS (molecular weight 13500) (low viscosity silicone oil), 0.5 parts of polymethyltriethoxysilane, 0.5 parts of hydrogen-containing silicone oil, 0.5 parts of platinum catalyst, 30 parts of aluminum hydroxide and 70 parts of aluminum oxide respectively, and then place aluminum hydroxide and aluminum oxide in an oven at 120℃ for 2 hours to dry.

[0038] (2) Weigh out low molecular weight vinyl silicone oil, polymethyltriethoxysilane, and hydrogen-containing silicone oil and pour them into a mixer. Connect a constant temperature water tank and control the temperature at 25°C. Control the mixer speed at 35 rpm and stir for 15 minutes. After stirring, add dried aluminum hydroxide and aluminum oxide to the mixer and stir repeatedly for 20 minutes each time. After the first stirring, turn on the vacuum pump to ensure that the vacuum degree in the mixer reaches below -0.1 MPa and continue stirring. After stirring, add platinum catalyst and stir for 15 minutes. After completion, thermally conductive silicone resin I is obtained.

[0039] (3) Divide the thermally conductive silicone resin obtained in step (2) into two equal parts, A and B. Add the ultra-high molecular weight vinyl silicone oil weighed in (1) and an additional 4 parts of hydrogen-containing silicone oil to part B and stir in a mixer for 8-15 minutes. After stirring, thermally conductive silicone resin II is obtained. First, press the A obtained in step (2) into a calendering device. Set the oven temperature to 120℃, add glass fiber preform, set the calendering thickness, which is thicker than the strength layer, and perform calendering and vulcanization to obtain a conventional single-layer thermally conductive pad with added glass fiber. This single-layer thermally conductive pad has the adhesion required by the customer.

[0040] (4) The single-layer thermally conductive pad obtained in (3) is wound up and then transferred to a calendering device for secondary calendering. The thermally conductive silicone resin II obtained in step (3) is then calendered and then placed in an oven for secondary vulcanization to produce a new type of double-sided thermally conductive pad with different properties.

[0041] Example 3

[0042] (1) Weigh out 30 parts of 200,000 CPS viscosity vinyl silicone oil (molecular weight approximately 175,000), 15 parts of 500 CPS viscosity vinyl silicone oil (molecular weight approximately 17,000), 0.5 parts of polymethyltriethoxysilane, 0.8 parts of hydrogen-containing silicone oil, 0.5 parts of platinum catalyst, 20 parts of aluminum hydroxide and 80 parts of aluminum oxide respectively, and then place aluminum hydroxide and aluminum oxide in an oven at 120°C for 2 hours to dry.

[0043] (2) Weigh out low molecular weight vinyl silicone oil, polymethyltriethoxysilane, and hydrogen-containing silicone oil and pour them into a mixer. Connect a constant temperature water tank and control the temperature at 20℃. Control the mixer speed at 15 rpm and stir for 15 minutes. After stirring, add dried aluminum hydroxide and aluminum oxide to the mixer and stir twice, 8 minutes each time. After the first stirring, turn on the vacuum pump to ensure that the vacuum degree in the mixer reaches below -0.1 MPa and continue stirring. After stirring, add platinum catalyst and stir for 15 minutes. After completion, thermally conductive silicone resin I is obtained.

[0044] (3) Divide the thermally conductive silicone resin obtained in step (2) into two equal parts, A and B. Add the ultra-high molecular weight vinyl silicone oil weighed in (1) and an additional 6 parts of hydrogen-containing silicone oil to part B and stir in a mixer for 15 minutes. After stirring, thermally conductive silicone resin II is obtained. First, press the A obtained in step (2) into a calendering device. Set the oven temperature to 120°C, add glass fiber preform, set the calendering thickness, which is thicker than the strength layer, and perform calendering and vulcanization to obtain a conventional single-layer thermally conductive pad with added glass fiber. This single-layer thermally conductive pad has the adhesion required by the customer.

[0045] (4) The single-layer thermally conductive pad obtained in (3) is wound up and then transferred to a calendering device for secondary calendering. The thermally conductive silicone resin II obtained in step (3) is then calendered and then placed in an oven for secondary vulcanization to produce a new type of double-sided thermally conductive pad with different properties.

[0046] Effect Evaluation 1

[0047] like Figure 1 and Figure 2 As shown, dense small pores appear in the silicone layer of a 0.5 mm conventional silicone cloth calendered gasket, and oil separation occurs on the silicone surface of the 0.5 mm conventional silicone cloth calendered gasket.

[0048] And such Figure 3 and Figure 4 The thermally conductive silicone pad with different properties on both sides prepared in Example 1 of the present invention shows that the silicone layer after calendering with controlled reactant concentrations on both sides of the glass fiber preform has no dense pores, and the strength chromatographic oil is significantly reduced after calendering with controlled reactant concentrations on both sides of the glass fiber preform.

[0049] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a thermally conductive pad with different properties on both sides, characterized in that, It comprises the following steps: S1: mixing 10-30 parts of low molecular weight vinyl silicone oil, 1-2 parts of polymethyl triethoxysilane and 0.5-4 parts of hydrogen-containing silicone oil by weight, then adding 10-50 parts of aluminum hydroxide and 40-100 parts of alumina to mix twice, to obtain a mixed raw material; S2: adding 0.5-1 parts of platinum gold catalyst to the mixed raw material to mix three times, to obtain a heat-conducting silicone resin I; S3: coating the heat-conducting silicone resin I obtained in step S2 on one side surface of a glass fiber base cloth, then performing primary calendering vulcanization, and winding, to obtain a single-layer heat-conducting gasket with adhesion; S4: coating the heat-conducting silicone resin II on the side surface of the single-layer heat-conducting gasket without the heat-conducting silicone resin I, then performing secondary calendering vulcanization, to obtain the double-sided heat-conducting gasket with different properties; The heat-conducting silicone resin II is obtained by mixing 20-40 parts of ultrahigh molecular weight vinyl silicone oil in the heat-conducting silicone resin I; the low molecular weight vinyl silicone oil has a viscosity of 100-500 CPS and a molecular weight of 5000-20000; the ultrahigh molecular weight vinyl silicone oil has a viscosity of 100000-200000 CPS and a molecular weight of 100000-250000.

2. The production method according to claim 1, wherein In step S1, the temperature of the primary mixing is 20-25℃, the rotation speed is 15-35 rpm, and the time is 8-15 min.

3. The production method according to claim 1, wherein In step S1, the aluminum hydroxide and the alumina are dried at 110-130℃ for 1-2 h before the primary mixing.

4. The production method according to claim 1, wherein In step S1, the secondary mixing method is stirring, and the stirring is performed 2-3 times, each time for 8-20 min.

5. The production method according to claim 4, wherein In the secondary mixing, the vacuum degree is reduced to below -0.1 mpa after the first stirring is completed.

6. The production method according to claim 1, wherein In step S2, the tertiary mixing method is stirring, and the stirring time is 14-16 min.

7. The production method according to claim 1, wherein In step S3, the temperature of the primary calendering vulcanization is 90-120℃.

8. The production method according to claim 1, wherein In step S4, the mixing is performed by using a stirrer, and the stirring time is 8-15 min.

9. A double-sided heat-conducting gasket with different properties prepared by the preparation method of any one of claims 1-8.

Citation Information

Patent Citations

  • High-strength low-oil-output heat-conducting silica gel gasket and preparation method thereof

    CN114350157A

  • Thermal conductive silicone rubber composite sheet

    EP2308676A1